2007
DOI: 10.1063/1.2775325
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crystallinity and nonstoichiometric region on dielectric properties of SrTiO3 films formed on Ru

Abstract: The dielectric constant depending on the film thickness for SrTiO3 films formed on Ru was investigated after an annealing step at 600°C, which shows that the dielectric constant increased abruptly with the film thickness up to 20nm and then increased slightly, remaining relatively constant at a value of about 65. The abrupt increase was due to the crystallinity of SrTiO3 films. On the other hand, the slight increase was related to the existence of nonstoichiometric region near the interface of SrTiO3 film and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The noble metals, such as Pt and Ru, are preferentially considered for use as electrode materials. [6][7][8][9][10][11][12] In addition to high work functions, these noble metals have sufficiently low resistivities that ultrathin films can be employed. Furthermore, these noble metals are able to minimize the device's leakage current, and they appear to have better chemical compatibility with the dielectrics than more conventional capacitor electrode materials such as TiN.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The noble metals, such as Pt and Ru, are preferentially considered for use as electrode materials. [6][7][8][9][10][11][12] In addition to high work functions, these noble metals have sufficiently low resistivities that ultrathin films can be employed. Furthermore, these noble metals are able to minimize the device's leakage current, and they appear to have better chemical compatibility with the dielectrics than more conventional capacitor electrode materials such as TiN.…”
mentioning
confidence: 99%
“…To maintain the required cell capacitance (25-30 fF/cell) in dynamic random access memory (DRAM) with design rules of 45 nm or less, high-k dielectric materials, such as ZrO 2 , TiO 2 , Ta 2 O 5 , SrTiO 3 , and (Ba,Sr)TiO 3 , have been extensively investigated. [1][2][3][4][5][6][7][8][9] For this application to be successful, the choice of a suitable capacitor electrode material is very important. The capacitor electrode material should not react with oxygen.…”
mentioning
confidence: 99%
“…The use of oxygen plasma for partially crystallized STO was also reported, and the dielectric constant of the resulting STO was 65 at 50 nm. 85 showed that the crystallinity of thermally grown ALD BTO could be improved by a remote oxygen plasma treatment after deposition (i.e., post-deposition treatment); 64 the dielectric constant of the ALD BTO increased by about a factor of 2 after extensive exposure (3 hours) to remote oxygen plasma due to the partial crystallization of the BTO film surface. Prinz et al also reported the PEALD of BTO films with remote oxygen plasma.…”
Section: Use Of Plasma (Intra-deposition and Post-deposition)mentioning
confidence: 99%
“…In this section, we review characterization strategies that researchers have pursued to understand the morphology of thin-film perovskites and how they linked their findings to the obtained properties (Table 5). 15,46,[64][65][66]70,72,[76][77][78][79][80][81]83,[85][86][87]90,94,97,98,102,[104][105][106] To obtain compositional information, XPS is the most common technique. The information that can be obtained ranges from film contamination to the elemental composition within the topmost 1-10 nm of the film and its uniformity, chemical and electronic states, binding information, and depth information.…”
Section: Characterization Of Ultrathin Perovskite Filmsmentioning
confidence: 99%
“…However, in an applicable thickness range for a DRAM capacitor, the dielectric constant of the SrTiO 3 thin film decreases abruptly when the thickness decreases due to inadequate crystallinity. [7][8][9][10] For enhancement of the dielectric properties of SrTiO 3 films, a strontium ruthenate ͑SRO͒ layer, which is formed by the deposition of an ultrathin SrO layer on Ru and postannealing in N 2 ambient, was introduced as a seed layer in our previous report. 11 As a conductive oxide material, SrRuO 3 has a pseudocubic perovskite structure with a lattice constant of 3.93 Å.…”
mentioning
confidence: 99%